Can Social Norms Promote Recycled Water Use on Campus? The Evidence From Event-Related Potentials - Liu, Xiaojun; Chen, Shiqi; Guo, Xiaotong; Fu, Hanliang (Frontiers in Psychology, 2022)
The unwillingness of college students to use recycled water has become a key barrier to sewage recycling on campus, and it is critical to strengthen their inclination to do so. This paper used college students in Xi’an as a case study and adopted event-related potential technology to explore the effect of social norms on the willingness to use recycled water and the neural mechanism of cognitive processing. The results suggested that: (1) The existence of social norms might influence college students' willingness to use recycled water. (2) When individuals' willingness to use recycled water is lower than the social norm, there is a bigger feedback-related negative amplitude. (3) College students pay more attention to social norms in groups with closer social distance. These findings can be used to provide a scientific basis for persuading the public to use recycled water from the perspective of the social norm to drive public acceptability.